Analisis Konten Informasi Dalam Laporan Keuangan, Laporan Kinerja dan Laporan Penyelenggaraan Pemerintah Daerah - Sukartini; Amy Fontanella (Akuntansi dan Manajemen, 2017)
Local government in Indonesia are obliged to produce at least 3 types of reports namely financial statements (LKPD), accountability reports (LAKIP) and performance report (LPPD). These three types of reports is regulated by different legal rules, using different formats and evaluated by different institutions. This research aims to analyze the information content of local government reports. Some previous research found that the usefulness of information presented on these three types of reports are relatively limited, whereas it requires high cost, involving many human resources and require a lot of infrastructure support. Thereforethe analysis of information presented in thesethree report needs to be done.This research conducted on Sleman and Malang district. The data used in this study were collected through document review, in-depth interviews, observation and focus group discusion. This study found many repetition of information on these three types of reports. This reseach also found inconsistencies of data used in these threereport.